Exixtence of Indonesian Advocate Profession - Zamroni, M; ., . (International Journal of Engineering and Technology, 2018)
Hope to have legislation that specifically set while an umbrella in running materialize advocate profession, lawyers are more confident in addition to other law enforcement officials, such as judges, prosecutors and police, as well as respected as an equal partner in the law enforcement process. But the big question is how the existence of the profession of advocate Indonesia before and after the enlawment of Act Number 18 of 2003 concerning the Advocate, as well as any constraints that occur in their implementation. The rule of law relating to the profession of advocate before the enLawment of Act Number 18 of 2003 concerning The Advocate, scattered in various laws, such as Act Number 1 of 1946 on the Law of Criminal Code, Act Number 1 of 1950 on the Supreme Court, Emergency Act Number 1 of 1951 governing temporary measures to organize the unity of the pecking order and civil court events, and Herziene Indlandsch Regalement (HIR). Before the release of Act Number 18 of 2003 concerning Advocates, advocate the use of the term in prLawice there has been no standard for the profession. In various provisions of the legislation of any inconsistency pr. For example Act Number 14 of 1970, as has been replaced by Act Number 35 of 1999, and was replaced again by Act Number 4 of 2004 as well as the latter is replaced by Act Number 48 of 2009, regarding the power of Justice, to use the term legal aid and lawyers. Birth of the Act of the Republic of Indonesia Number 18 of 2003 concerning The Advocate is the expectation of a long delayed during the 58 years since the independence of the Republic of Indonesia, the laws governing the profession of advocate a free, independent and responsible for the implementation of a judicial honest, fair, and legal certainty for all seekers of justice in upholding the law, truth, justice, and human rights.Â Â